The PENGARUH PDRB DAN USIA PRODUKTIF TERHADAP PENYERAPAN TENAGA KERJA ERA BONUS DEMOGRAFI - Asia, Rama Putri; Rizqi, Firistya Sabrina; Faradilla, Silvia Putri; Nilasari, Aprillia; Arisetyawan, Kukuh (Jurnal Ekonomika : INDEPENDEN, 2024)
This study aims to analyze the impact of Gross Regional Domestic Product (GRDP) at current prices and the productive age population on labor absorption in Indonesia during the demographic bonus era. The demographic bonus is a period where the productive age population is larger than the non-productive population, offering opportunities to increase economic growth through higher employment absorption. Using secondary data from the Central Bureau of Statistics (BPS) and various panel data regression analysis methods, this study finds that GRDP and the productive age population significantly influence labor absorption in Indonesia. These results highlight the importance of policies that support job creation to fully capitalize on the potential of the demographic bonus. Keywords: Demographic Bonus, GRDP, Labor Absorption, Productive Age